2011
DOI: 10.1002/asia.201100721
|View full text |Cite
|
Sign up to set email alerts
|

Rasta Resin–PPh3–NBniPr2 and its Use in One‐Pot Wittig Reaction Cascades

Abstract: A new triarylphosphine-tertiary amine bifunctional polymeric reagent has been prepared and used effectively in a variety of one-pot Wittig reactions. The design of this reagent resolved a deficiency of a previously reported related material, and allowed it to perform more efficiently in such reactions. Furthermore, it was readily recyclable, and was also successfully applied in cascade processes involving one-pot Wittig reactions followed by either a conjugate reduction or a reductive aldol reaction. In these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 109 publications
2
8
0
Order By: Relevance
“…Since these reactions require the use of a base, we designed a bifunctional rasta resin, RR-NBniPr 2 -PPh 3 =O 18 (Scheme 5), which bears both triphenylphosphine oxide and tertiary amine moieties, in order to increase the efficiency and appeal of our method. We have extensive experience in preparing functionalized resins with two different catalytic groups [3538], and prepared 18 by oxidation of 19 , which we previously used as a bifunctional reagent in one-pot Wittig reactions [29]. Gel-phase 31 P NMR spectroscopic analysis of 18 indicated that oxidation of the phosphine groups was complete, and elemental analysis was used to determine the loading level of phosphine oxide and amine groups to be 1.07 mmol/g and 1.06 mmol/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since these reactions require the use of a base, we designed a bifunctional rasta resin, RR-NBniPr 2 -PPh 3 =O 18 (Scheme 5), which bears both triphenylphosphine oxide and tertiary amine moieties, in order to increase the efficiency and appeal of our method. We have extensive experience in preparing functionalized resins with two different catalytic groups [3538], and prepared 18 by oxidation of 19 , which we previously used as a bifunctional reagent in one-pot Wittig reactions [29]. Gel-phase 31 P NMR spectroscopic analysis of 18 indicated that oxidation of the phosphine groups was complete, and elemental analysis was used to determine the loading level of phosphine oxide and amine groups to be 1.07 mmol/g and 1.06 mmol/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently we have studied the use of the rasta resin polystyrene architecture [1926] as a platform for reagents and catalysts [2733], and have used easily synthesized rasta resin–Ph 3 P ( 14 ) in various Wittig reactions that required only filtration and solvent removal for product purification (Fig. 1) [2729]. Additionally, 14 was converted into phosphonium salt 15 , which proved to be an efficient and highly recyclable catalyst for aldehyde and ketone cyanosilylation reactions from which the products could also be obtained pure after only filtration and solvent removal [30].…”
Section: Introductionmentioning
confidence: 99%
“…The conjugate addition to furnish the silyl enol ether can be combined with a reductive Aldol reaction, where for the Wittig reaction and for the reductive Aldol reaction two separate aldehydes can be used (Scheme 22) [145]. The reactions above can be run with a triarylphosphinetertiary amine bifunctional polymeric reagent (Rasta-Resin-PPh 3 -NBn i Pr 2 ), where the polymer bound triarylphosphine oxide also exerts a catalyzing effect on the addition of Cl 3 SiH while making it possible to recycle the polymer [146].…”
Section: Alkenesmentioning
confidence: 99%
“…83 Stabilised phosphoranes provide Wittig-products predominantly in E-configuration. [74][75][76][77][78][79][80][81][82][83] Initially, for HWE reactions, two types of polymer bound reagents, one a phosphonate 84 and one a phosphinate, 85 were examined, evidently to facilitate the separation of water soluble olefination products from the anionic phosphorus side-products. 86 In the first case, polystyryl-ethanol was treated with trimethylphosphite [P(OMe) 3 ] and then methyl bromoacetate, to give methyl 2-polystyrylethylmethoxycarbonylmethylphosphonate.…”
Section: Wittig-and Horner-wadsworth-emmons-olefination With Polymer mentioning
confidence: 99%
“…Wittig transformations with polymer bound Wittig ylides are known. [75][76][77][78][79][80][81][82][83][84] Phenylated phosphines on polystyrene-type backbones have become commercially available. Thiemann et al 82 have used p-poly(styryldiphenyl-phosphine) 33 to prepare polymer bound halophenacylmethylidenephosphoranes 36, which could be derivatised by C-C bond forming reactions such as by Suzuki cross-coupling reactions (Scheme 10).…”
Section: Wittig-and Horner-wadsworth-emmons-olefination With Polymer Bound Reagentsmentioning
confidence: 99%